Factors affecting the interest of specialized assistants to continue studying in subspecialized fields: a brief report - Ghazal Mansouri; Fatemeh Nouri Koohbanani; Fatemeh Karami Robati; Robabe Hosseinisadat (Tehran University Medical Journal, 2024)
Background: Choosing a specialty in medicine is an important decision for the individual. It is also important decision for the health system. This study aimed to investigate the factors affecting the interest of specialized assistants to continue studying in subspecialized fields. Methods: This descriptive cross-sectional study investigated the factors affecting the interest of 261 specialized assistants to continue their studies in subspecialized fields from March 2021 to March 2022. All the specialized assistants of Kerman University of Medical Sciences (KMU), whose assistantship continued until the end of March 2022, were included in the study by census method. The data collection tool was a 4-part questionnaire. 1) demographic information including 13 questions (age, gender, marital status, city where the family lives, place of residence to complete the residency course, specialized field, level of education, grade point average, parents' education, parents' occupation and having first-degree relatives with subspecialized degrees), 2) the willingness or unwillingness to continue studying in subspecialized fields and the field of interest, 3) the reasons for the assistants' interest in continuing their education, included 14 questions, and 4) the reasons for the assistants' lack of interest in continuing their education, included 14 questions.